THE CONCEPT OF "BACKGROUND COMPONENT" IN IASA SOFTWARE MODEL. - SAADI, ABDELFETAH; BENNOUAR, DJAMEL; HENNI, ABDERRAZEK (Courrier du Savoir; Vol. 14 (2012): Courrier du Savoir)
This  article  describes  a  new  approach  for  software  component  architecture  to  deal  with  dynamic  adaptation  of  software systems. We  introduced  the concept of "Background Component"  in our  IASA software component model. The Background components  are a  set  of  components  that  run at  the  back  ground  level  to  adapt  dynamically  the  software  architecture. The proposed  approach  is  close  to  that  of  intelligent  agents  which manage  all  types  of  events  during  the  deployment  or  the implementation of the architecture.